Dopaminergic modulation of ganglion-cell photoreceptors - Van Hook, Matthew J. (2012)
A novel class of photoreceptors, the intrinsically photosensitive retinal ganglion cells (ipRGCs), expresses the photopigment melanopsin and drives non-image-forming responses to light such as circadian photoentrainment, the pupillary light reflex, and suppression of nocturnal melatonin production in the pineal. Because dendrites from one subclass of these cells – the M1-type ipRGCs – make presumptive synaptic contacts at sites of dopamine release from dopaminergic amacrine cells, they are prime targets for modulation by dopamine, a neuromodulator implicated in retinal circadian rhythms and light adaptation. In patch-clamp recordings from ipRGCs in intact rat retinas, dopamine attenuated the melanopsin-based photocurrent. We confirmed that this was the result of direct action on ipRGCs by replicating the effect in dissociated ipRGCs that were isolated from influences of other retinal neurons. In these recordings, the D1-family dopamine receptor agonist SKF38393 attenuated the photocurrent, caused a modest depolarization, and reduced the input resistance of ipRGCs. The D2-family agonist quinpirole had no effect on the photocurrent. Single-cell RT-PCR revealed that the majority of ipRGCs tested expressed drd1a, the gene coding for the D1a dopamine receptor. This finding was supported by immunohistochemical localization of D1a receptor protein in melanopsin-expressing ganglion cells. Finally, the adenylate cyclase activator forskolin, applied in combination with the phosphodiesterase inhibitor IBMX, mimicked the effects of SKF38393 on the ipRGC photocurrent, membrane potential, and input resistance, consistent with a D1-receptor signaling pathway. These data suggest that dopamine, acting via D1-family receptors, alters the responses of ipRGCs and thus, of non-image-forming vision.